Healthcare-associated respiratory infections in intensive care unit can be reduced by a hand hygiene program: A multicenter study. Issue 6 (November 2018) - Finco, Gabriele; Musu, Mario; Landoni, Giovanni; Campagna, Marcello; Lai, Alberto; Cabrini, Luca; Sardo, Salvatore; Mura, Paolo; Galletta, Maura
Abstract: Purpose: Healthcare-associated respiratory tract infections are common and markedly affect the quality of life and mortality, as well as increasing costs for health systems due to prolonged hospitalisation. This study aimed to assess the change in both level and trend of respiratory tract infections after a specific hand hygiene program for intensive care unit (ICU) staff. Materials and methods: The infection data collection was carried out from January 2013 to August 2014. The hand hygiene program started in December 2013. To analyse the change in level and trend of infections after the intervention, the Interrupted Time Series method was used. Chi-square test was used to compare the incidence of respiratory tract infections before and after the intervention. Results: A total of 825 patients were hospitalised in three Italian ICUs. The infection level was significantly decreased by 36.3 infections per 1000 device-days after the intervention. The infection trend was also decreased of about 1 infection per month. Conclusions: After the hand hygiene program a decreased level of infection was found. Continuous performance feedback should be provided to promote a long-term adherence to the guidelines. Organisational and individual risk factors must be individuated and correctly managed to increase quality of practice.